Two cases of severe neonatal hypertrophic cardiomyopathy caused by compound heterozygous mutations in the MYBPC3 gene - Deprez, R H Lekanne (BMJ Group, 2006)
BACKGROUND: Idiopathic (primary) hypertrophic cardiomyopathy (HCM) is mainly caused by mutations in genes encoding sarcomeric proteins. One of the most commonly mutated HCM genes is the myosin binding protein C (MYBPC3) gene. Mutations in this gene lead mainly to truncation of the protein which gives rise to a relatively mild phenotype. Pure HCM in neonates is rare and most of the time childhood HCM occurs in association with another underlying condition. OBJECTIVE: To study the presence of mutations in the MYBPC3 gene in idiopathic childhood HCM. METHODS: MYBPC3 coding region and splice junction variation were analysed by denaturing high performance liquid chromatography (DHPLC) and sequencing in DNA isolated from two neonates with severe unexplained HCM, who died within the first weeks of life. RESULTS: Truncating mutations were found in both alleles of the MYBPC3 gene in both patients, suggesting there was no functional copy of the MYBPC3 protein. Patient 1 carried the maternally inherited c.2373_2374insG mutation and the paternally inherited splice‐donor site mutation c.1624+1G→A. Patient 2 carried the maternally inherited frameshift mutation c.3288delA (p.Glu1096fsX92) and the paternally inherited non‐sense mutation c.2827C→T (p.Arg943X). CONCLUSIONS: The findings indicate the need for mutation analysis of genes encoding sarcomeric proteins in childhood HCM and the possibility of compound heterozygosity.